Essential oils modulate virulence phenotypes in a multidrug-resistant pyomelanogenic Pseudomonas aeruginosa clinical isolate - Jayalekshmi Haripriyan; Christy Rose Binu; Nitasha D Menon; Muralidharan Vanuopadath; Malavika B. Hari; N Namitha; Kesiya Binoy; Anil Kumar; Bipin G. Nair; Victor Nizet; Geetha B. Kumar (Scientific Reports)
Abstract Pyomelanogenic P. aeruginosa, frequently isolated from patients with urinary tract infections and cystic fibrosis, possesses the ability to withstand oxidative stress, contributing to virulence and resulting in persistent infections. Whole genome sequence analysis of U804, a pyomelanogenic, multidrug-resistant, clinical isolate, demonstrates the mechanism underlying pyomelanin overproduction. Seven essential oils (EOs) were screened for pyomelanin inhibition. Garlic, cinnamon and thyme EOs were selected for further studies based on their significant anti-virulent properties, like inhibition of pyomelanin production and biofilm formation. Additionally, downregulation of the expression of virulence genes regulated by quorum sensing (QS) and a decrease in levels of the QS signaling molecule, C12-HSL, were also observed. The EO treatment inhibited the survival of U804 in human blood and increased survival of C. elegans, a whole animal model of pathogenesis. EO treatment also resulted in a significant reduction of efflux pump activity, indicative of their effect on antibiotic sensitization. Garlic oil enhanced the permeability of the bacterial membrane, resulting in decreased survival, when combined with sub-MIC concentrations of colistin. This study demonstrates that thyme, cinnamon and garlic EOs can attenuate pyomelanogenic P. aeruginosa virulence traits. Additionally, garlic potentiates drug sensitivity, suggesting its promising therapeutic use in combating pyomelanogenic MDR infections.